Effects of smoking on delayed neuropsychiatric sequelae in acute carbon monoxide poisoning: A prospective observational study. Issue 20 (21st May 2021) - Nah, Sangun; Choi, Sungwoo; Lee, Sun-Uk; Kim, Gi Woon; Lee, Young Hwan; Han, Sangsoo
Abstract : Abstract: Smoking is a well-known risk factor for cardio-cerebrovascular disease. However, several studies have reported the "smoker's paradox" whereby smokers have a better prognosis for cardio-cerebrovascular diseases. Similar to cardio-cerebrovascular diseases, hypoxia is one of the major mechanisms of injury in carbon monoxide (CO) poisoning. This study investigated the association between smoking and delayed neuropsychiatric sequelae (DNS) in acute CO poisoning. This study involved patients with CO poisoning treated at a university hospital in Bucheon, Korea between September 2017 and March 2020. The exclusion criteria were age <18 years, discharge against medical advice, loss to follow-up, persistent neurological symptoms at discharge, transfer from another hospital 24 hours after exposure, and transfer from another hospital after hyperbaric oxygen therapy. Logistic regression analysis was performed to find factors associated with DNS. Two hundred sixty three patients visited the hospital due to CO poisoning and of these, 54 were excluded. DNS was evaluated up to 3 months after discharge, and until this time, DNS occurred in 35 (16.8%) patients. And the incidence rate of DNS was lower in smokers than non-smokers (15, 12% vs 20, 23.8%, P  = .040). Multivariable logistic regression analysis revealed that CO exposure time (odds ratio [OR] 1.003; confidence interval [CI] 1.001–1.005; P  = .003), the Glasgow coma scale (GCS) (OR 0.862; CI 0.778–0.956; P  = .005), and pack-years (OR 0.947; CI 0.903–0.993; P  = .023) were statistically significant for DNS development. These results indicate that more pack-years smoked were associated with reduced risk of the development of DNS in acute CO poisoning, and that CO exposure time and GCS is a predictive factor for DNS occurrence. Abstract : Supplemental Digital Content is available in the text